Determinación del comportamiento de consumo horario residencial de agua potable de las parroquias Cubijíes y San Gerardo - Macas Tixe, Romey Anderson (2024)
Nowadays the drinkable water intake is of great importance for all mankind, even becoming indispensable in each inhabitant’s lifestyle. The Ecuadorian water supply system comes from various water sources, which after undergoing its purification process are distributed to residential areas. To this day, there are cities where there is a need to supply this water demand, but factors such as population growth and the lack of updates in the current regulative laws have led to poor management of the supply systems. Therefore, it is of such importance the understanding of the hourly behavior of residential water consumption. The present research analyses the residential water consumption behavior in San Gerardo, canton Guano, and Cubijíes, canton Riobamba. The following networks were identified: Filtro de la Cruz-Cubijíes y Olte San Pedro-San Gerardo. By applying the stratification method proposed by Arellano et al., (2012), three socioeconomic strata B, C, and D were identified for both distribution networks, with the absence of strata A. The most important factors influencing water consumption are the number of users living in the households, sanitary units, storage units, and water quality. In the field study, readings were taken for 104 water meters in both networks, 54 were from Filtro de la Cruz-Cubijíes and 50 from Olte San Pedro-San Gerardo. By obtaining the hourly consumption curves, it was defined the maximum flow rates (Qmax) of each network. In Filtro de la Cruz-Cubijíes there is a maximum flow rate of 125.00 l/h that was recorded at 12:00 while in Olte San Pedro-San Gerardo was 118.90 l/h recorded at 13:00. Finally, the variation coefficients (Kh) were determined based on the CPE INEN 5 standard (1992), where the value range fluctuates from 2.00 to 2.30. Both networks exceed the maximum range, with Filtro de la Cruz-Cubijíes being at 2.46 and Olte San Pedro-San Gerardo at 2.52.